A Mycobacterium avium subsp. paratuberculosis relA deletion mutant and a 35 kDa major membrane protein elicit development of cytotoxic T lymphocytes with ability to kill intracellular bacteria - Gaber S. Abdellrazeq; Mahmoud M. Elnaggar; John P. Bannantine; Kun T. Park; Cleverson D. Souza; Brian Backer; Victoria Hulubei; Lindsay M. Fry; Samy A. Khaliel; Helmy A. Torky; David A. Schneider; William C. Davis (Veterinary Research, 2018)
Abstract Efforts to develop live attenuated vaccines against Mycobacterium avium subspecies paratuberculosis (Map), using indirect methods to screen Map deletion mutants for potential efficacy, have not been successful. A reduction in the capacity to survive in macrophages has not predicted the ability of mutants to survive in vivo. Previous studies for screening of three deletion mutants in cattle and goats revealed one mutant, with a deletion in relA (ΔMap/relA), could not establish a persistent infection. Further studies, using antigen presenting cells (APC), blood dendritic cells and monocyte derived DC, pulsed with ΔMap/relA or a 35 kDa Map membrane protein (MMP) revealed a component of the response to ΔMap/relA was directed towards MMP. As reported herein, we developed a bacterium viability assay and cell culture assays for analysis and evaluation of cytotoxic T cells generated against ΔMap/relA or MMP. Analysis of the effector activity of responding cells revealed the reason ΔMap/relA could not establish a persistent infection was that vaccination elicited development of cytotoxic CD8 T cells (CTL) with the capacity to kill intracellular bacteria. We demonstrated the same CTL response could be elicited with two rounds of antigenic stimulation of APC pulsed with ΔMap/relA or MMP ex vivo. Cytotoxicity was mediated through the perforin granzyme B pathway. Finally, cognate recognition of peptides presented in context of MHC I and II molecules to CD4 and CD8 T cells is required for development of CTL.